Features of discrete VLF emissions observed at Gulmarg, India during the magnetic storm of 6–7 March, 1986 - Singh, Rajesh; Singh, A.K.; Siingh, Devendraa; Singh, R.P. (My University, 2007)
During the analysis of archived VLF data from Indian low latitude ground stations, some discrete VLF emissions recorded at the low latitude ground station Gulmarg (geomagnetic latitude 24°26′N; geomagnetic longitude 147°09′E, L = 1.28) during moderate magnetic storm activity (Σ K P − = 32, K P index varies from 4 to 6 during the observation period) on 6/7 March, 1986 are presented in this paper. The dynamic spectra of these discrete VLF emissions were observed along with tweeks and its harmonics, which is interesting and complex to explain. In most of the events the harmonic frequency of tweeks correlates with the starting frequency of harmonics of discrete emissions. In order to explain the observed features of discrete VLF emissions, we propose cyclotron resonance interaction between whistler mode wave and energetic electrons of inner radiation belt as possible generation mechanism. An attempt is also made to determine parallel energy, anisotropy and wave growth relevant to the generation process of VLF emissions.
Keywords: Magnetospheric physics; Space plasma physics; Wave particle interactions; Waves and instabilities; VLF emissions; Upper atmosphere; Magnetic storm